Sex-role orientation: Differences among students and teachers - Richardson, Arthur G. (1988)
The Bem Sex Role Inventory was administered to 408 secondary school students and 393 teachers, randomly selected from seven Caribbean states. This article analyses indicated marked differentiation of males (both teachers and students) and females (both teachers and students) in sex-role orientation. Students were more rigidly sex-typed than were teachers
DOI: 10.2224/sbp.1988.16.2.165
Keywords: Gender analysis